Pengembangan Aplikasi Dewan Masjid Indonesia (DMI) Berbasis Ekonomi Umat Dengan Metode Waterfall - Winarsih, Nurul Anisa Sri; Fanani, Ahmad Zainul; Saraswati, Galuh Wilujeng; Rohman, Muhammad Syaifur (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The conventional economic system has been developing for a long time, followed by the Islamic economic system which is currently developing rapidly in Indonesia. Sharia economic activities are based on the rules of the Koran regarding right and wrong, good and bad, and halal and haram rules. The background of sharia business ethics is the Prophet Muhammad SAW which is based on the Al-Quran and Hadith. The sharia economy can be seen with the emergence of Islamic banks, almost all major banks in Indonesia have sharia branches. Not only that, e-money and sharia payment gateways already exist. This is based on the large number of Indonesian people who adhere to Islam and the increasing awareness of Muslims in Indonesia in implementing the Islamic economic system. Since March 2, 2020, the Corona virus or Covid-19 pandemic has entered Indonesia. Many employees become unemployed. 50% of MSMEs could go bankrupt in the next few months. Whereas small businesses make a big contribution to the absorption of jobs in Indonesia which creates income for the population. The management of the Semarang City DMI organization took the initiative to ease the burden on the people, especially in the city of Semarang by making the DMI application based on the people's economy. Waterfall is the method used in this research. Waterfall is suitable for application development with a complete needs analysis. After the PSBB period ended, there were many unemployed who tried their luck by selling small businesses and MSMEs opened slowly. It is hoped that the DMI application can introduce the business of the community around the mosque and other people can buy the business easily through the application.